2017
DOI: 10.18805/ag.r-1732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mulching on soil and water conservation -A review

Abstract: The need to increase food production and improve the quality of our environment has prompted a search for materials to control wind and water erosion. This paper is a review of research and development associated with application, methods, and amounts of mulch types-crop residues, chemical soil stabilizers, and feedlot wastes (manure)-required to control wind erosion. An effective wind erosion control treatment is one that can resist a 38.0 m/s wind as measured at 15.2 m. Mulching has becomes an important prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…The incorporation of biochar into the soil can alter soil physical properties such as structure, pore size distribution and water holding capacity (Downie et al, 2009). Improved soil structure facilitate the infiltration of water and reduce the runoff and soil erosion (Sharma and Bhardwaj, 2017). Vithanage et al (2014) reported biochar amended soils reduce the soil loss by 19.9% compared to untreated area.…”
Section: Application Of Manuresmentioning
confidence: 99%
“…The incorporation of biochar into the soil can alter soil physical properties such as structure, pore size distribution and water holding capacity (Downie et al, 2009). Improved soil structure facilitate the infiltration of water and reduce the runoff and soil erosion (Sharma and Bhardwaj, 2017). Vithanage et al (2014) reported biochar amended soils reduce the soil loss by 19.9% compared to untreated area.…”
Section: Application Of Manuresmentioning
confidence: 99%
“…Nail weeder, apart from efficient weed control, also provides advantages of soil mulch in crop field, which might have resulted in better moisture conservation [24] and regulated soil temperature [25] which might be reflected in gradual microbes build up upto 45 DAS. Several reports [26], Sharma and Bhardwaj [27] in support of mulching effects on soil health had been already registered. Thus the total count of each of the three microbes turned out maximum in case of Nail weeder at 7 DAS + Quizalofop ethyl 5 EC at 60 g/ha at 30 DAS (T5) keeping statistical parity with the Pretilachlor treated plot in count of bacteria and actinomycetes.…”
Section: Soil Microbial Populationmentioning
confidence: 99%
“…For instance, these areas are gently sloping, have medium textured soils, and the major type of land use is agriculture. Mulching is applied in agricultural areas to reduce the rate of runoff [31]. The very high suitable areas receive an average annual rainfall of above 1000mm.…”
Section: Mulchingmentioning
confidence: 99%